2019
DOI: 10.1038/s41467-019-09182-1
|View full text |Cite
|
Sign up to set email alerts
|

Staged developmental mapping and X chromosome transcriptional dynamics during mouse spermatogenesis

Abstract: Male gametes are generated through a specialised differentiation pathway involving a series of developmental transitions that are poorly characterised at the molecular level. Here, we use droplet-based single-cell RNA-Sequencing to profile spermatogenesis in adult animals and at multiple stages during juvenile development. By exploiting the first wave of spermatogenesis, we both precisely stage germ cell development and enrich for rare somatic cell-types and spermatogonia. To capture the full complexity of spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
199
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(247 citation statements)
references
References 88 publications
(123 reference statements)
17
199
1
1
Order By: Relevance
“…We observed its accumulation in spermatogonia, pachytene spermatocytes, round spermatids and elongated spermatids, and it accumulated on the X chromosome in round spermatids, as reported in previous studies [55][56][57][58]. At the pachytene stage of meiosis I, genes on sex chromosomes are transcriptionally shut down by meiotic sex chromosome inactivation (MSCI) and are reactivated after meiosis [59,60], to which H3K9me3 is reported to be involved [55]. It was also revealed that if there was no enrichment of H3K9me3, remodeling and silencing of sex chromosomes failed and resulted in germ cell apoptosis [49].…”
Section: Discussionsupporting
confidence: 90%
“…We observed its accumulation in spermatogonia, pachytene spermatocytes, round spermatids and elongated spermatids, and it accumulated on the X chromosome in round spermatids, as reported in previous studies [55][56][57][58]. At the pachytene stage of meiosis I, genes on sex chromosomes are transcriptionally shut down by meiotic sex chromosome inactivation (MSCI) and are reactivated after meiosis [59,60], to which H3K9me3 is reported to be involved [55]. It was also revealed that if there was no enrichment of H3K9me3, remodeling and silencing of sex chromosomes failed and resulted in germ cell apoptosis [49].…”
Section: Discussionsupporting
confidence: 90%
“…Oatley and colleagues have demonstrated that the Id4-eGFP bright A undiff population is highly enriched for SSC activity. However, conclusions from these studies suffer some limitations due to (1) use of early postnatal mice where the niche and SSCs themselves are different from the adult counterparts (Ernst et al 2019) and (2) flow cytometric-based sorting of cells for transplantation studies compared activity of Id4-eGFP bright versus Id4-eGFP dim populations but functional capabilities and identity of an abundant population expressing intermediate levels of the Id4 reporter were not characterized (Chan et al 2014, Helsel et al 2017. Moreover, recent independent assessments of Id4 expression by single-cell RNA sequencing, immunostainings and use of independent mouse reporter lines have demonstrated that Id4 expression is substantially more widespread within the A undiff (or male germline in general) than previously described (Hermann et al 2018, La et al 2018a, Kitadate et al 2019, La et al 2018b.…”
Section: Undifferentiated Male Germ Cellsmentioning
confidence: 99%
“…Beyond identifying discrete cell populations corresponding to mature cell types and states, scRNA-seq can identify developmental trajectories in diverse systems, such as in the developing embryo, in adult stem cell populations and even during tumor progression (Behjati et al, 2018;Marioni and Arendt, 2017;Tritschler et al, 2019 in this issue). Recent applications of scRNA-seq in developmental systems include the analysis of hematopoiesis (Athanasiadis et al, 2017;Macaulay et al, 2016) and spermatogenesis (Ernst et al, 2019;Green et al, 2018;Guo et al, 2018;Hermann et al, 2018;Wang et al, 2018;Xia et al, 2018 preprint), and the analysis of embryogenesis in zebrafish, frog and mouse (Briggs et al, 2018;Cao et al, 2019;Farrell et al, 2018;Pijuan-Sala et al, 2019;Wagner et al, 2018). The increasing amount of data generated by such studies also enables us to identify minor cell types and hitherto unappreciated cell states during development, and their interactions with the neighboring environment.…”
Section: Scrna-seq Raises New Challenges For Studies Of Developmentalmentioning
confidence: 99%